2010
DOI: 10.1186/1477-7525-8-114
|View full text |Cite
|
Sign up to set email alerts
|

Association between treated/untreated traumatic dental injuries and impact on quality of life of Brazilian schoolchildren

Abstract: BackgroundTraumatic dental injury (TDI) could have physical and psychosocial consequences for children. Thus, it is important to measure the impact of TDI on the quality of life of children (QoL). The aim of the present study was to investigate the association between treated/untreated TDI and the impact on the quality of life of 11-to-14-year-old Brazilian schoolchildren.MethodsA cross-sectional study was carried out involving 1612 male and female schoolchildren aged 11 to 14 years attending public and privat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
118
8
24

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(162 citation statements)
references
References 19 publications
7
118
8
24
Order By: Relevance
“…Results also indicate that dental caries was not significantly associated with social well-being domain of OHRQoL (O'brien et al, 2007;Bendo et al, 2010).This is in contrast with those reported by Krisdapong et al (2012), who reported that caries had a significant impact on the daily activities of participants. One has to keep in mind the different tools used for measuring child OHRQoL by different researchers.…”
Section: Discussion:-contrasting
confidence: 75%
“…Results also indicate that dental caries was not significantly associated with social well-being domain of OHRQoL (O'brien et al, 2007;Bendo et al, 2010).This is in contrast with those reported by Krisdapong et al (2012), who reported that caries had a significant impact on the daily activities of participants. One has to keep in mind the different tools used for measuring child OHRQoL by different researchers.…”
Section: Discussion:-contrasting
confidence: 75%
“…OHRQoL indices show buccal and dental disorders can impair social, psychological and physical activities, and disturb children's functional performance such as eating and speaking, psychological performance such as showing teeth and smiling without embarrassment, and social performance by damaging their social life [9,[11][12][13][14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…Em estudos avaliando o impacto que as fraturas de esmalte e dentina não restauradas [28][29] e restauradas 30 causaram na vida diária dos escolares, o traumatismo dentário apresentou grande impacto na qualidade de vida dos adolescentes suscitando limitações em suas atividades diárias como sociabilizar, sorrir, mastigar e pronunciar determinadas palavras.…”
Section: Resultsunclassified